Association of Ergonomic Risk Exposure with Cholesterol Levels in Workers Aged Over 40 Years at PT. X Electronics Manufacturing Batam, 2025 - Maulina, Diina; Krismadies, Krismadies; Kartika Wijaya, Juhanda; Sarbiah, Andi; Rahmani, Ardhi Arsala (Rifa'Institute, 2025)
Introduction: Elevated cholesterol levels among workers aged over 40 years constitute an important risk factor for cardiovascular disease. Work conditions with ergonomic risk exposures such as static postures, repetitive movements, and limited rest periods are presumed to contribute to disturbances in lipid metabolism. Objective: This study aimed to analyze the association between ergonomic risk exposure and cholesterol levels among older workers at PT. X Manufacturing Elektronik Batam. Method: A cross-sectional design was employed involving 173 respondents. Data were collected through ergonomic observations, questionnaires, and laboratory examinations of total cholesterol. Result and Discussion: Bivariate analysis using the Chi-square test revealed that workers with static postures had a higher prevalence of dyslipidemia (36.7%) compared to those with non-static postures (19.2%) (p=0.083). Workers with high repetitive movements also showed a higher prevalence of dyslipidemia (37.0%) compared to those with light–moderate repetition (18.5%) (p=0.063). Furthermore, workers with inadequate rest had a higher prevalence of dyslipidemia (57.1%) compared to those with adequate rest (31.8%) (p=0.143). Although the results were not statistically significant, the observed trends indicate a potential relationship between ergonomic risk factors and cholesterol levels. Conclusion: These findings provide an important foundation for future longitudinal studies and ergonomic interventions aimed at preventing metabolic disorders in the workplace